Pengaruh Model Pembelajaran Problem Based Learning Terhadap Pemahaman Konsep IPA Siswa Kelas 4 SD Negeri Doyong 4 Kota Tangerang - Hidayati, Nurul Dwi; Sunardin, Sunardin; Magdalena, Ina (Jurnal Ilmiah Wahana Pendidikan, 2023)
Nurul Dwi Hidayati "The Influence of the Problem Based Learning Learning Model on the Understanding of Science Concepts in Class 4 SD Negeri Doyong 4 Tangerang City". This study aims to determine the effect of the Problem Based Learning learning model on students who use conventional methods. This study used a quasi-experimental design with nonequivalent control group design. The population subjects in this study were all fourth grade students at SD Negeri Doyong 4 Kota Tangerang totaling 56. The sample used was saturated sampling, namely class IV A, totaling 24 students as the control class and IV B, totaling 28 students as the experimental class. The data collection technique uses an instrument to test the ability to understand concepts in the form of an essay consisting of 10 questions that are valid and reliable. Based on the initial analysis, the initial abilities of the two classes have the same abilities. While the results of the study showed that the average posttest value for the control class was 27.85 while in the experimental class it was 40.83. This is based on the t-test showing the value of tcount = 5.205 and ttable 2009. It can be concluded that there is a significant difference between the average posttest scores. control class and experimental class. This can be interpreted that the ability to understand science concepts using the Problem Based Learning learning model is higher than using conventional learning methods.